Site-selective oral delivery of therapeutic antibodies to the inflamed colon via a folic acid-grafted organic/inorganic hybrid nanocomposite system - Sang Hoon Lee; Jae Geun Song; Hyo-Kyung Han (Elsevier, 2022)
This study aimed to develop a pH-responsive folic acid-grafted organic/inorganic hybrid nanocomposite system for site-selective oral delivery of therapeutic antibodies. A folic acid-grafted aminoclay (FA-AC) was prepared via an in situ sol‒gel method. Then, a drug-loaded nanocomplex was prepared via the electrostatic interaction of FA-AC with infliximab (IFX), a model antibody, and coated with Eudragit® S100 (EFA-AC-IFX). FA-AC exhibited favorable profiles as a drug carrier including low cytotoxicity, good target selectivity, and capability to form a nanocomplex with negatively charged macromolecules. A pH-responsive FA-AC-based nanocomplex containing IFX (EFA-AC-IFX) was also obtained in a narrow size distribution with high entrapment efficiency (>87%). The conformational stability of IFX entrapped in EFA-AC-IFX was well maintained in the presence of proteolytic enzymes. EFA-AC-IFX exhibited pH-dependent drug release, minimizing premature drug release in gastric conditions and the upper intestine. Accordingly, oral administration of EFA-AC-IFX to colitis-induced mice was effective in alleviating the progression of ulcerative colitis, while oral IFX solution had no efficacy. These results suggest that a pH-responsive FA-AC-based nanocomposite system can be a new platform for the site-selective oral delivery of therapeutic antibodies.